2022
DOI: 10.3389/fonc.2022.809159
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Assessment of Lymph Node Metastasis in Patients With FIGO Stage IB1 Cervical Cancer

Abstract: ObjectivesTo assess the risk factors of lymph node metastasis (LNM) in patients with FIGO stage (2009) IB1 cervical cancer (CC).MethodsPatients with FIGO stage IB1 CC who underwent radical resection between 2012 and 2018 were recruited. The risk factors for LNM were analysed. A recursive partitioning analysis (RPA) was used to divide the patients into risk groups and assess their risk of LNM.ResultsThe 5-year overall survival rate was 91.72%, while 80.0% and 93.5% for patients with or without LNM (P<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The five-year overall survival rate for early-stage cervical cancer is greater than 90% [ 25 ]. LNM significantly reduces patient survival [ 26 ]. According to Hosaka et al, in patients with stage IB-IIB cervical cancer, the five-year overall survival (OS) rate was 94.8% in those without LNM [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The five-year overall survival rate for early-stage cervical cancer is greater than 90% [ 25 ]. LNM significantly reduces patient survival [ 26 ]. According to Hosaka et al, in patients with stage IB-IIB cervical cancer, the five-year overall survival (OS) rate was 94.8% in those without LNM [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was initially classified as IB1 stage with endogenous tumor (size > 4cm), but according to 2018 FIGO staging the patient would have been classified as IB3 stage (equivalent to 2009 FIGO stage IB2). LVSI, deep stromal invasion, and tumor size are all known to be powerful predictors of LNM in CC patients 30 . It has also been reported that preoperative prediction of LNM in CC can be improved by including radiomics in the nomogram 12 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…To predict the pCR rates of the patients with LARC after NCRT, the RPA was performed to classify patients with LARC into different risk groups. RPA was a useful statistical method for predicting patient risk in a number of cancers, including colorectal cancer, nasopharyngeal cancer, cervical cancer, and breast cancer, which could assist clinicians to determine the best medication regimen (30,(47)(48)(49). However, few studies used the RPA to forecast the NCRT response in patients with LARC.…”
Section: Discussionmentioning
confidence: 99%
“…There were more pieces of evidence that pelvic fat was related with the inflammatory response. PNI is a novel index to reflect the nutritional and inflammatory status of patients, and its clinical efficacy as a predictive factor in different malignancies has been established ( 47 , 48 ). In the present study, we found that both the PNI and MPA scores were effective at predicting NCRT response in patients with LARC.…”
Section: Discussionmentioning
confidence: 99%